2015
DOI: 10.1021/acs.jpca.5b02031
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Descriptors of Yttria-Stabilized Zirconia at Low Defect Concentration: An ab Initio Study

Abstract: Keywords: solid oxide fuel cell, yttria stabilised zirconia, cubic zirconia, bixbyite yttria, ab initio, density functional theory, empirical potential, Born-Mayer-Huggins, point charge model, phonons, harmonic approximation. been observed in either X-ray or neutron diffraction experiments. The prediction of local defect structure and the interaction between defects is therefore of great interest. This has not been possible to date as the number of possible defect topologies is very large and to perform reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…41,42 As pointed out in the last paragraph, each of the three processing techniques reveals different dopant distributions, which only in one case represents the thermodynamic equilibrium configuration with the lowest energy. Doping of HfO 2 [25][26][27][43][44][45] and ZrO 2 46 was extensively researched utilizing the density functional theory (DFT) and using cluster expansion 30,33,47 or high-throughput calculations 48 under the premise that the lowestenergy structure is realized in thin films. Although all these studies attempt to answer the question of phase stabilization with doping, they do not consider the energy variation from the doping distribution enforced and biased by the processing technique.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 As pointed out in the last paragraph, each of the three processing techniques reveals different dopant distributions, which only in one case represents the thermodynamic equilibrium configuration with the lowest energy. Doping of HfO 2 [25][26][27][43][44][45] and ZrO 2 46 was extensively researched utilizing the density functional theory (DFT) and using cluster expansion 30,33,47 or high-throughput calculations 48 under the premise that the lowestenergy structure is realized in thin films. Although all these studies attempt to answer the question of phase stabilization with doping, they do not consider the energy variation from the doping distribution enforced and biased by the processing technique.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations on defect interaction often con-sidered defect pairs and found that energies are lower for an Y ion in the NNN (next nearest neighbor) cation shell of an oxygen vacancy, compared to Y in the NN (nearest neighbor) cation tetrahedron of the vacancy or interaction-free vacancies, even though calculated absolute values of defect interaction energies vary considerably. 11,13,18,19,22,24 This defect interaction also strongly depends on the dopant ion. 15,23,24 Defect energies were further calculated for more extended defects of several dopant ions and oxygen vacancies, [30][31][32] and such studies as well as experimental data 33 showed the relevance of vacancy-vacancy interaction.…”
mentioning
confidence: 99%
“…First, we focused on the static non-linear optical properties of pure c-ZrO 2 aiming at a reliable estimation of the order of magnitude of its third order NLO responses in idealized conditions to be used as a guide for our qualitative conclusions. Since little is known about the true local atomistic structure of YSZ, to circumvent the challenging task [25,26] of determining the most stable local crystal structure of each system considered, the second step comprised computations addressing the importance of the vacancy/dopant distribution on the third order susceptibilities. For this task, we chose two doping concentrations of 3.2 and 33 %mol.…”
Section: First-principle Calculationsmentioning
confidence: 99%
“…These are the pure Perdew, Burke, and Ernzerhof (PBE) [31] exchange-correlation functional, its hybrid counterpart PBE0 [32] and the Becke, three-parameter, Lee-Yang-Parr exchange-correlation functional (B3LYP). [33] The first two functionals, namely PBE and PBE0, have been used in previous studies, [25,34] involving the structural and electronic properties of YSZ while the popular B3LYP, was chosen in order to check the robustness of the results. All periodic calculations have been performed at the static limit with a developer s version of CRYSTAL17 software [35] that allows analytic computations of non-linear optical (NLO) properties of infinite periodic systems.…”
Section: First-principle Calculationsmentioning
confidence: 99%
See 1 more Smart Citation